(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the results of research conducted in cooperation with "IDEAL TEKSTIL-ORZU" LLC. The main goal of the research is to determine the effectiveness of improving the quality of women’s outerwear production using leather scraps and the introduction of new resource-saving technologies. The operational characteristics (strength, durability, aesthetic appearance) of the developed sample "Set of Seasonal Women’s Clothing" were evaluated and compared with similar products available on the market. The results showed that the new method is effective not only in improving the quality and aesthetics of the product, but also in significantly reducing material and labor costs.